The effect of different activation irrigations on intracanal smear layer removal: a vitro study - Wang, Lingxiang; Feng, Bo; Shi, Shaojing; Sun, Degang; Wu, Di (Frontiers in Bioengineering and Biotechnology, 2024)
Objective: To compare the effect of syringe irrigation technique, passive ultrasonic activation technique, EDDY activation technique and Er,Cr,YSGG laser activation technique on smear layer removal in root canals in vitro. Methods: Forty mandibular first premolars with single canal were collected from patients in Qingdao Stomatological Hospital affiliated to Qingdao University. After root canal preparation with ProTaper Universal to F3, they were randomly divided into four groups (n=10) according to different activation irrigations for the final washing: syringe irrigation(SI), passive ultrasonic activation(PU), EDDY activation (EDDY) and Er,Cr,YSGG laser activation (YSGG). Finally, all the crowns of them were cut off and the root length was trimmed to 15mm. The roots were split longitudinally and observed with scanning electron microscope (SEM) for assessment of smear layer removal in different parts of the root canal. Results: All groups showed similar effects for cleaning the root canals in the coronal thirds (P>0.05). For cleaning the root canals in the middle thirds, PU group, EDDY group and YSGG group showed similar effects, (P>0.05).They were more effective than SI group (P < 0.05). For cleaning the root canals in the apical thirds, PU group and EDDY group showed similar effects (P>0.05). They were more effective than SI group (P < 0.05). YSGG group was more effective than other groups (P < 0.05). Conclusions: Er,Cr,YSGG laser activation technique can remove smear layer of root canals effectively. The cleaning effect of the passive ultrasonic activation technique, EDDY activation technique is better than that of syringe irrigation technique.